Climate uncertainty and economic development: Evaluating the case of Mozambique to 2050 - Channing Arndt; James Thurlow (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
We apply a probabilistic approach to the evaluation of climate change impacts in the Zambeze River Valley. The economic modeling relies on an economywide modeling approach. Taking a distribution of shocks as inputs, we create hybrid frequency distributions of the potential economic impacts of climate change for Mozambique. The approach identifies an explicit range of potential outcomes and associates a probability with given sets of outcomes. For example, we find that the economy of Mozambique may be up to 13% smaller in 2050 due to the effects of climate change. However, the chance of GDP losses of less than 5% are more than four out of five with about 10% of these outcomes actually positive. Large declines in GDP, defined as a decline greater than 10%, are the result of a dramatic reduction in flood return periods though the probability of large declines is relatively small at 2.5%. We conclude that this probabilistic approach provides significantly more information to policy makers and productively focuses scientific effort and the agenda for future research.
Keywords: O13; Q54; Q56; 330; Climate change; uncertainty; economic impacts; economywide model; Mozambique; Klimawandel; Makroökonomischer Einfluss; Mosambik